UNCROWNED NOVEL DIPTYCH BY DITA TABORSKA - Gilk, Erik (Bohemica Olomucensia, 2020)
The paper deals with two novels written by Dita Taborska (*1981), a newcomer in contemporary Czech literature. Her literary works Malinka (2017) and Besa (2018) are connected with the same topic and some of the figures. We can determine her proses as psychological and social novels with the dominant topic of interpersonal relations, especially among parents and their children (also adoptive ones). The author of the paper analyses especially narrative methods and construction of the main figures in Taborska's novels and also summarizes their critical reception.
Keywords: Czech literature after 1989; Czech fiction; adoption; Dita Taborska